ANALISIS LOYALITAS KONSUMEN BERDASARKAN KUALITAS PRODUK DAN PROMOSI PADA MINUMAN TRADISIONAL BIR PLETOK BABEH BOYO JAKARTA - Yusup, Iskandar; Sulistiani, Sinta (Journal of Research and Publication Innovation, 2024)
This research aims to analyze product quality and marketing strategies towards consumer loyalty to the traditional beer Pletok "Babeh Boyo" drink. This research is qualitative research with a descriptive approach. The data sources obtained are primary and secondary data. Data collection methods used interviews, observation, Key Informants, and FGD (Forum Group Discussion). Researchers use confirmability tests. Data analysis techniques use EFAS, IFAS, IE Matrix, and SWOT Matrix. The results of this research state that the Analysis of Product Quality and Marketing Strategy on Consumer Loyalty has a close relationship or has an influence on consumer loyalty. This is stated in several consumer statements that they are satisfied with the product quality and marketing obtained in the Traditional Beer Pletok Drink "Babeh Boyo" The sense of satisfaction felt by consumers results in loyal consumers and they can recommend them to others.